The THE KURDISH EPIC BETWEEN FOLKLORE AND CLASSICAL LITERATURE: THE EPICS OF (MAM AND ZIN) AND (ZANBIL FROSH) AS A MODEL - Nuri, Hersh; Abdullah, Bakir (Humanities Journal of University of Zakho, 2026)
The epic, as a literary genre, narrates a lengthy experience and is structured according to poetic forms. This genre holds significant value and importance in Kurdish literature, with its roots tracing back to ancient times among the Kurdish people. It has served as a mirror and echo of the victories and defeats of the Kurdish nation, while also documenting Kurdish history. Initially, Kurdish epics consisted of various verses and poetic compositions, recited by poets and folk singers. The Kurds celebrated these narratives, which evolved through their contributions. Over time, this form of art became a fundamental and robust foundation for another literary genre. Kurdish poets transformed the oral verses and folk poetry, traditionally shared verbally among people, into an advanced and developed literary form through the process of transcription. This transition marked a shift from oral tradition to written expression, as these verses were recorded, thus elevating them from the realm of oral narration to that of literature. Subsequently, they were re-recorded and disseminated within the framework of classical literature. This research, titled "The Kurdish Epic Between Folkloric and Classical Literature: The Case of Mem and Zin and Zembil Farosh," addresses the literary significance of folkloric and classical epics both in content and form. It aims to theoretically and practically interpret these epics while distinguishing between them. Through this study, we have sought to analyze the Kurdish literary epics and differentiate them through the term "epic," as applied to classical epics, particularly focusing on "Mem and Zin" by the poet Ahmad Khani, which serves as a primary reference. Additionally, we utilize verses from "Zembil Farosh" in our analysis. In conclusion, we arrived at the following findings: the verses of "Zembil Farosh" are imbued with religious content, while the epic "Mem and Zin" is centered around themes of love and romance, albeit expressed in divergent forms and styles.